(untitled) (Journal of Hama University, 2024)
This study aimed to perform a clinical and radiographic evaluation of pulpotomy in pulpitis permanent teeth using BC and MTA materials. Follow up for come year to evaluate the success rate of this treatment. Materials and Methods: The research sample consisted of twenty permanent teeth with irreversible pulpitis in sixteen patients. The research sample were divided into two main equal groups according to the used Material (BIOCERAMIC, MTA). Pulpotomy results through 6-12 months were evaluated clinically and radiologically assess the success rate of the treatment.. This study showed that there were no statistically significant differences in the success rate BC group and MTA group, according follow -up periods (after six months, after one year) Conclusion: Vital pulp Therapy using BC and MTA showed a high success rate after 12 months follow up period in permanent teeth suffering pulpitis, so this vital pulp therapy can be an alternative technique to traditional endodontic treatments.